Hubungan Perilaku Hidup Bersih Dan Sehat Dan Fisik Rumah Dengan Kejadian Ispa Pada Balita Di Wilayah Kerja Puskesmas Beriang Tinggi Kabupaten Kaur Tahun 2021 - Zolendo, Nano Setiawan; Felizita, Epina; Suyanto, Jifri (Universitas Dehasen Bengkulu, 2022)
Upper respiratory tract infection (ARI) is a problem of acute inflammation of the upper and lower respiratory tract. Acute respiratory infections are caused by viruses or bacteria. Data from the world health organization in 2020 there are approximately 960,000 children under five who died and this was caused by ISPA (WHO, 2020). The prevalence of ARI in children under five by province based on basic health research in 2018 in Bengkulu province was 14% of 100,000 residents (RI Ministry of Health, 2018). And based on data from the Kaur District Health Office the number of ISPA sufferers in 2020 was 1,486 (Kaur District Health Office, 2020). This research uses a descriptive quantitative research type with an analytic survey research method using a Cross Sectional design. This research was conducted by collecting data and direct observation of the respondents at the same time. The population that has been studied is all mothers who have toddlers in the Beriang Tinggi Working Area, Kaur Regency in 2021, totaling 354 mothers who have toddlers. The sampling technique in this study is the snowball sampling technique. So the sample in this study were 188 mothers. The results of this study are that there is a relationship between clean and healthy living behavior and the incidence of respiratory infections in toddlers in the Working Area of the Beriang Tinggi Health Center, Kaur Regency, in 2021, there is a relationship between home ventilation and the incidence of respiratory infections in toddlers in the Work Area, Beriang Tinggi Health Center, Kaur Regency, in 2021, there is a relationship between the floor of the house with the incidence of respiratory infections in toddlers in the Working Area of the Beriang Tinggi Health Center, Kaur Regency in 2021 and there is a relationship between the walls of the house and the incidence of respiratory infections in toddlers in the Work Area of the Beriang Tinggi Health Center, Kaur Regency in 2021. It is hoped that the study program results from this research can be developed and added to insight and can add knowledge to other students